Visual quotes and physical activity tracking: Can aesthetic pleasure motivate our short-term exercise motivation? - Duro, Lígia; Karapanos, Evangelos; Campos, Pedro F.; Romão, Teresa (My University, 2019)
Empirical studies of activity tracking in HCI research have paid little attention to the impact of the visual presentation of motivational text messages on exercise motivation, even though, these days, motivational texts are often embedded in a visual presentation (such as visual quotes). Herein, we report the results of an online experiment with a total of 368 participants. Contrary to expectations, perceived aesthetic pleasure did not strengthen the motivating capability of perceived positive or neutral motivational text messages on the type of exercise motivation linked to the short-term (on the extrinsic-identified behavior regulation). Findings are discussed in the context of physical activity tracking services.
Keywords: Aesthetic pleasure; Exercise motivation; Motivational text messages